Application of the Guided Inquiry Learning Model to Improve Student Creativity and Activeness in the Teaching and Learning Process Biology Education Study Program - Ruth Megawati (Jurnal Penelitian Pendidikan IPA, 2023)
One of the qualities of learning is determined by the learning process. Therefore, the accuracy of the teacher is required in diagnosing and determining appropriate learning strategies in the classroom. This research is classroom-in-action research carried out for 1 semester with the aim of increasing student creativity and activeness in the learning process in basic biology courses. The techniques and instruments used are, Observation, Test using an evaluation sheet. In addition, several students will be interviewed to confirm the data that has been obtained. Data analysis was carried out in a quantitative descriptive manner, and the results of the interviews will be explained according to the facts found. The results of the study with indicators of the success of this study, namely 75% of the guided inquiry model were carried out well and students completed classically. The results showed that the implementation of the guided inquiry model was in the well-implemented category, creativity, and learning outcomes increased by 80% from cycle I to cycle II. Based on the results and discussion of the research, it can be concluded that the guided inquiry learning model can increase creativity and student learning outcomes in basic biology courses